Biosimilar granulocyte–colony‐stimulating factor for mobilization of autologous peripheral blood stem cells in pediatric hematology‐oncology patients. Issue 2 (29th July 2014) - Cesaro, Simone; Tridello, Gloria; Prete, Arcangelo; Dallorso, Sandro; Cannata, Elisa; Massaccesi, Erika; Risso, Marco; De Bortoli, Massimiliano; Caselli, Désirée
<x xml:space="preserve">Abstract</x> Background Recently biosimilars of granulocyte–colony‐stimulating factor (G‐CSF) became available for prophylaxis and treatment of postchemotherapy neutropenia and for mobilization of peripheral blood CD34+ cells for either autologous or allogeneic hematopoietic stem cell transplant. Most of the data on the mobilization efficacy and safety of biosimilar G‐CSF are from adult patients, whereas no data are available in pediatric patients. Study Design and Methods This was a retrospective study on cases treated at three Italian pediatric transplant centers, from January 2011 to October 2013. Data were collected on all children undergoing first peripheral blood stem cell (PBSC) mobilization after stimulation with biosimilar G‐CSF and chemotherapy. The results were compared with a historical control group. Results Twenty‐nine children underwent mobilization with biosimilar G‐CSF. Peak peripheral blood CD34+ cell count of 20 × 106/L was achieved in 90% of patients, with a median value of 71 × 106/L. Eighty‐three percent reached the desired target (CD34+/kg) dose. The median number of collected CD34+ cells was 10 × 106/kg (range, 4.8 × 106‐68.8 × 106/kg). No difference was observed in comparison with historical control group mobilized with originator filgrastim. Moreover, no major and/or unexpected side effects were reported. Conclusion Biosimilar G‐CSF resulted as effective and safe as originator filgrastim molecule in mobilizing PBSCs in children, with the advantage of a reduced cost.